Removal of Endocrine Disrupting Compounds in Drinking Water: A Review - Sun, Yongjun; Zheng, Huaili; Teng, Houkai; Xue, Wenwen; Zhao, Weican; Zhang, Zhengan; Liao, Yi; Xu, Zhinan (Asian Journal of Chemistry, 2014)
The article reviews the information regarding endocrine disrupting compounds, including the definition of endocrine disrupting compounds, the present pollution situation in China and the treatments. Various natural chemicals and some contaminants of industrial source were classified as endocrine disrupting compounds. For the endocrine disrupting compounds could adversely affect reproductive and developmental health, it was necessary and meaningful to discuss the applicable removal methods fand processes. In this review, a number of treatment processes were discussed in terms of their potential on removal of endocrine disrupting compounds. Finally, the future prospects together with the challenges for the monitoring and removing the endocrine disrupting compounds from water were summarized.